Hydrogenolysis of glycerol over TiO2-supported Pt-WOx catalysts: Effects of the TiO2 crystal phase and WOx loading - Wang, Yaju; Zhou, Zhiming; Wang, Chao; Zhao, Leihong; Xia, Qineng (Frontiers in Chemistry, 2022)
The selective hydrogenolysis of glycerol to 1,3-propanediol (1,3-PDO) with high added value is attraction but challenging. Pt-WOx-based catalysts have been extensively studied in the selective hydrogenolysis of glycerol. The catalyst support and the physicochemical state of WOx play important roles on this reaction. In this paper, Pt-WOx catalysts supported on TiO2 with different crystal forms were prepared and studied for their catalytic performance in hydrogenolysis of glycerol. It was observed that the catalytic performance of anatase-type (A-type) TiO2-supported catalyst (Pt/W/A-Ti) is much better than that of the rutile-type (R-type) TiO2 catalyst (Pt/W/R-Ti) due to its higher stability. Furthermore, the influence of W loading amount and state were thoroughly investigated for the Pt/W/A-Ti catalysts, and Pt/W/A-TiO2 with 5 wt% loading of WOx achieved the best catalytic performance (100% conversion of glycerol and 41% yield of 1,3-PDO under the optimal reaction conditions), owing to the suitable WOx domains and high dispersion of W species, as evidenced by XRD patterns and TEM images. Mechanism study by in-situ DRIFTS experiments indicated that glycerol was first converted to 3-hydroxypropanal and then converted to 1,3-PDO through subsequent reactions.